Regional anaesthesia for clavicular surgeries - A systematic review - Dr. Isha Chopra,; Dr. Sushil Chhabra,; Dr. Diksha, (GMC Patiala Journal of Research and Medical Education, 2023)
The clavicle gets sensory innervation from both the cervical plexus as well as brachial plexus with variable contribution. This review was done to determine if regional anaesthesia with ultrasound can serve as the sole anaesthetic technique for clavicular surgeries.